Vitamin C from the baobab - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1996)
The baobab tree is widely distributed throughout the semi-arid areas of sub-Saharan Africa. It is a tree with many uses: the barkand rind are used for cord fibres and fuel, the young leaves are used in sauces and the powdery pulp of the fruit...